Penerapan Pembelajaran Berdeferensiasi Dengan Model Discovery Learning Dalam Meningkatkan Hasil Belajar Ppkn Pada Siswa Kelas XII MIPA IV SMA Negeri 1 Maros - Abdul Rahman; Andrian Andrian; Muhammad Nawir (Universitas Palan, 2024)
This study aims to explore the effect of applying differentiated learning model with Discover Learning model on learning outcomes of Pancasila and Civics Education (PPKn) in class XII MIPA IV SMA Negeri 1 Maros Regency. The research method used was classroom action research (PTK) with a double cycle design. The research participants consisted of 36 students of class XII MIPA IV SMA Negeri 1 Maros. consisting of various ability levels. Learning outcome data were collected through tests and observations. The results showed that the application of differentiated learning model with Discover Learning model can improve Civics learning outcomes in students of class XII MIPA IV SMA Negeri 1 Maros. There were significant improvements in concept understanding, critical thinking skills, and learning motivation of learners after the application of this learning model. This finding shows that the use of differentiated learning model with Discover Learning model can be an effective alternative in improving Civics learning outcomes in students of class XII MIPA IV SMA Negeri 1 Maros.